Structural and Extralinguistic Aspects of Code-Switching: Evidence From Papiamentu-Dutch Auditory Sentence Matching - Suurmeijer, Luuk; Parafita Couto, M. Carmen; Gullberg, Marianne (Frontiers in Psychology, 2020)
Despite a wealth of studies on effects of switch locations in code-switching (CS), we know relatively little about how structural factors such as switch location and extralinguistic factors such as directionality preferences may jointly modulate CS (cf., Stell & Yapko, 2015). Previous findings in the nominal domain suggest that within-constituent switching (within the noun phrase) may be easier to process than between-constituent switching (a structural effect), and that there may also be directionality effects with switches preferred only in one language direction (an extra-linguistic effect). In this study we examine a different domain, namely how VP-external (preverbal) vs. VP-internal (postverbal) switch location and switch directionality affects the processing of Papiamentu-Dutch mixed subject-verb-object (SVO) sentences. We manipulated switch location (preverbal/postverbal), and directionality of switch (PD/DP) and tested 50 Papiamentu-Dutch bilinguals on an auditory sentence matching task. The results from the mixed conditions showed no effect of switch location. Instead, we found only an effect of directionality and in an unexpected direction for this population, with switches from Dutch to Papiamentu being processed faster than switches from Papiamentu to Dutch regardless of switch location. The results highlight the importance of taking extralinguistic factors into account, but also the challenges of studying CS, particularly in lesser studied speech communities, and the need for a data-driven, cross-disciplinary approach to the study of CS.